Austenite grain growth calculation of 0.028% Nb steel - Priadi D.; Napitupulu R.A.M.; Siradj E.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Modeling of microstructural evolution has become a powerful tool for materials and process design by providing quantitative relationships for microstructure, composition and processing. Insufficient attention has been paid to predicting the austenite grain growth of microalloyed steel and the effect of undissolved microalloys. In this research, we attempted to calculate a mathematical model for austenite grain growth of 0.028% Nb steel, which can account for abnormal grain growth. The quantitative calculation of austenite grain growth generated from this model fit well with the experimental grain growth data obtained during reheating of niobium steels. The results of this study showed that increasing the temperature increases the austenite grain size, with a sharp gradient observed at higher temperatures.